Competitiveness of Rhizobium leguminosarum bv. phaseoli strains in relation to environmental stress and plant defense mechanisms - Wolff, AB; Streit, W; Kipe-Nolt, Judith A.; Vargas, H.; Werner, D. (Springer, 1991)
Six Rhizobium leguminosarum bv. phaseoli strains (Ciat 151, Ciat 895, Ciat 899, CE3, H2C, Kim5s) were tested for nodule occupancy in different bean cultivars at two field sites (one fertile, one acid tropical soil) and in the greenhouse. The effects of several environmental factors such as low pH, high temperature, Al and Mn toxicity, iron deficiency, bean tannins, and bean phytoalexins were tested in vitro. Strain Kim5s was competitive under all tested conditions while strains CE3 and H2C had consistently low nodule occupancy levels. Strain Ciat 151 was superior to the other inoculant strains in the acid soil but competed poorly in the fertile soil. Strain Ciat 895 was more competitive in the fertile soil. There was a decline in nodule occupancy for all strains tested from the first trifoliate leaf stage to the pod-filling stage. No plant genotype effect on nodule occupancy was observed. There were significant (P<0.05) plant genotype and location effects, but no significant strain effect on acetylene reduction activity, plant dry weight, and nodule number. The greenhouse experiments confirmed, at least partially, the results from the field trials. In Leonard jars with an acid soil, strains Ciat 151 and Kim5s were amongst the most competitive strains. In coinoculation experiments, Kim5s was the most competitive strain, followed by Ciat 899 and Ciat 895. The competitiveness of a given strain was affected by the coinoculant strain. Tolerance in vitro to low pH, high growth temperature, Al or Mn toxicity, or Fe limitation was not related to competitiveness of the inoculum strains. The sensitivity of the strains towards bean tannins or bean phytoalexins also was not correlated with their competitiveness.